Efficacy of exenatide, ozone, and methyl prednisolone for the recovery of infraorbital nerve paresthesia after injury in rats - Mehdi Abrishami; Arash Golestaneh; Laleh Maleki; Hasan Momeni; Mazyar Manshaei (Wolters Kluwer Medknow Publications, 2021)
Background: Infraorbital nerve injury often occurs due to zygomatic complex fracture. There is no standard protocol to restore the sensory and motor function of the nerve after injury. Some medications are used to improve nerve function. This histopathological animal study aimed to assess the neurotrophic efficacy of exenatide, ozone, and methyl prednisolone for injured infraorbital nerve. Materials and Methods: In this animal study, 60 rats were randomly divided into five groups (n = 12) of control, saline, methyl prednisolone, exenatide, and ozone. Under general anesthesia, a unilateral infraorbital incision was made, and the nerve was compressed with a hemostat for 5 s. Depending on the study group, the rats received the designated medications. All rats were sacrificed after 14 days, and the nerve recovery was evaluated by observing the slides prepared from the area under a light microscope using histological and immunohistochemical parameters. Data were analyzed using Chi-square test and Tukey's least significant difference test (P < 0.05). Results: No inflammation in the peripheral tissue had a significantly higher frequency in the methyl prednisolone group (P < 0.05). Degeneration, intracellular inflammatory infiltrate, muscle injury, fibrosis around the nerve, granulation tissue, vascular proliferation, and infiltration of inflammatory cells around the nerve were more commonly absent in the exenatide group (P < 0.05). Conclusion: Exenatide showed superior efficacy for the recovery of infraorbital nerve function after injury. Thus, it may be beneficial for postoperative care following infraorbital nerve injury.